Effect of Late Testing and Antiretroviral Treatment on Mortality Among People Living With HIV in the Era of Treat-All in Guangdong Province, China, 1992–2018: A Cohort Study - Chen, Qiaosen; Liu, Jun; Fu, Xiaobing; Yang, Fang; Liu, Qicai; Li, Junbin; Tan, Zhimin; Li, Jing; Lin, Kaihao; Yan, Yao; Yang, Yi; Li, Yan; et al. (Frontiers in Public Health, 2022)
Late testing and antiretroviral treatment (ART) prevailed among people living with HIV (PLHIV) and impacted the benefit from immediate ART. This study aimed to identify the benefit of test-and-immediate-treat policy in China, the effect of immediate ART, and the influence of late testing and ART among the whole PLHIV in Guangdong Province, China. We designed two tendency analyses in aggregative form and two cohorts (surveillance and ART cohort) in individuals’ perspectives based on the HIV/AIDS Comprehensive Response Information Management System. Two interrupted time series models were conducted for tendency analysis from 2009 to 2018 to explore the all-cause and short-term mortality decrease after the test-and-immediate-treat policy. A time-dependent Cox model was performed for the surveillance cohort from 1992 to 2018, and a joint model was utilized for the ART cohort to identify the effect of immediate ART and the influence of late testing and ART on death. The tendency analysis included 324,914 and 68,679 person-years for all-cause/short term mortality. 49,289 and 26,287 PLHIV were recruited in surveillance and ART cohort with 5,557 and 459 death, respectively. The short-term mortality dropped from 4.69 cases/100 person-year in January of 2009 to 0.35 case/100 person-year in December of 2018 (Standardized rate). The all-cause mortality saw a decreasing trend from 1.46 cases/100 person-year in January of 2009 to 0.14 cases/100 person-year in December of 2018 (Standardized rate). The tendency analysis showed a significant short-term mortality slope decrease after the test-and-immediate-treat policy (P=0.024). From the surveillance cohort, late testing, in general, was a risk factor of all-cause mortality (hazard ratio (HR)=1.330, 95% confidence interval (CI), 1.250, 1.416). ART cohort showed higher hazards of all-cause mortality among PLHIV with no late testing but late ART (HR=1.690, 95%CI, 1.166, 2.451) and both late testing and late ART (HR=1.335, 95%CI, 1.042, 1.710). Immediate ART might decrease the hazard of all-cause death though it is insignificant (HR=0.923, 95%CI: 0.755, 1.129) in the ART cohort. The test-and-immediate-test policy brought the benefit to PLHIV. We should enlarge the HIV testing using comprehensive approaches to decrease the late testing and ART and increase the benefit from immediate ART.